Building an RRG computational grammar1 - Cortés Rodríguez, Francisco; Mairal-Usón, Ricardo (Onomázein, 2016)
Several grammatical models have shown a growing interest for the development of the conditions necessary to satisfy the so-called criterion of computational adequacy. Within Role and Reference Grammar (RRG [Van Valin & LaPolla, 1997; Van Valin, 2005; Pavey, 2010]), there have been some works seeking to implement the model in different computational environments (Diedrichsen, 2011, 2013; Guest, 2009; Nolan & Periñán-Pascual, 2014; Salem et al., 2008). In this scenario, the works of Van Valin & Mairal (2014), Periñán-Pascual (2013) and PeriñánPascual & Arcas (2014) have set up the guidelines to devise a parsing system called ARTEMIS (Automatically Representing TExt Meaning via an InterlinguaBased System) for the computational treatment of the syntax and semantics of sentences. The goal of this paper is to contribute to the development of ARTEMIS focusing specifically on the design of the rules necessary for the effective computational parsing of unmarked simple clauses following the format of the Layered Structure of the Clause as described in RRG. Such rules should yield, as a result for every sentence, a parsed tree following the format of grammatical analyses in RRG.